Potentials and benefits of recreational fisheries development in Malaysia - Zakaria, Mohammad Zaidi; Ambak, Mohd Azmi (1990)
This paper examines the potentials for the development of recreational fisheries. The extent of human resources and natural resources available was highlighted. At present any resemblance of recreational fisheries in Malaysia is in the few 'fishing spot' such as the National Parks when the visitors are allowed to fish, in Lake Gardens of some cities and around some of the Islands (during 'fishing competition seasons'). Otherwise the enthusiastic recreationist or sport fisherman takes his own initiatives to fish in the unmanaged waters in the country. Emphasis was also given on the economic, health and tourism related benefits. In essence, our fishery resources can be managed and utilised for their recreational and aesthetic values. Recreational fishing development can be planned so as to pay back financially for its upkeep. In the near future, it can be developed countries such as the United States of America.